Parecoxib nel trattamento del dolore postoperatorio: considerazioni farmacoeconomiche - Pradelli, Lorenzo; Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2003)
Parecoxib sodium is the first selective COX- 2 inhibitor to be available for parenteral administration. This pharmaceutical feature, alongside its favorable efficacy and safety profile, makes the new drug particularly suitable for simple and effective management of post-surgical pain. The first part of the present article describes the most important pharmacological characteristics of parecoxib and reviews the main efficacy and safety studies that were performed on patients presenting with post-surgical pain. Starting from these clinical data, the second part outlines the pharmacoeconomical profile of the drug in the Italian setting, focusing on the comparison with parenteral ketorolac, the most widely prescribed treatment for post-surgical pain in Italy. The available scientific evidence suggests that the introduction of parecoxib in the arsenal of available options for the management of this kind of patients in Italy may have a positive clinical and economical impact, despite of the higher drug acquisition price. In particular, the better tolerability shown by parecoxib in the comparison with non-selective NSAIDs would permit a reduction in the costs for the prevention and the cure of drugrelated adverse events and reduce the need for patient monitoring. Furthermore, the improved safety and the longer duration of the analgesic action could allow the management of more minor surgery patients in daysurgery units, with great economical advantages for the hospital and the health system and improved quality of life for the patients.